Analisis Isi Pesan Dakwah dalam Akun @Nugarislucu pada Media Sosial Twitter dengan Studi Kasus Tanggal 01 Maret 2020 - 01 April 2020 - Risma Eko Prastiyo; Luthfi Hidayah (Busyro : Jurnal Dakwah dan Komunikasi Islam, 2020)
The background of this research is the @NUgarislucu account which has a unique characteristic where the account preaches in a different way, each da'wah has its own message and it is packed with humor or jokes. The platform used is social media Twitter which is now busy being used, especially by millennials. The research entitled "Analysis of the content of da'wah messages in the @NUgarislucu account on Twitter social media with a case study dated March 01, 2020 - April 01, 2020." The problem formulation is how the contents of the da'wah message are contained in the @NUgarislucu twitter account. The purpose of this study was to determine the contents of the da'wah message contained in the @NUgarislucu account. This study uses qualitative research methods and the approach used is content analysis while the data sources used are primary data sources and secondary data. The data can be obtained by direct observation on the @NUgarislucu account. Based on the data analysis that was carried out, it was concluded that the contents of the da'wah messages contained in the @NUgarislucu account include various things, including messages of aqidah da'wah, shari'a da'wah messages and messages of akhlaq da'wah. The message of preaching aqidah itself discusses religion and faith. The message of Islamic da'wah discusses worship and practice. And the last message of moral da'wah which discusses character and commendable deeds.